Causes and effects of unbalanced voltages serving an induction motor - Kersting, W.H. (IEEE transactions on industry applications, 2001)
A common requirement of a distribution system is to serve a combination of single-phase lighting loads and a three-phase induction motor. Two transformer connections for providing this combination service are the ungrounded wye-delta and the open wye-open delta. Each connection has its good points and bad points. Of concern are the three-phase voltages provided the induction motor. If the voltages are unbalanced, depending upon the degree of unbalance, the induction motor is subject to overheating. Sources of the voltage unbalance can be the unequal spacing between conductors of the primary and secondary lines, the transformer ratings and connection, and the amount of single-phase load relative to the three-phase load. This paper utilizes previously published models of the primary and secondary lines, transformer connections, and induction motors. A simple system is developed to demonstrate the voltage unbalance created by these components under normal and abnormal conditions and the effect of the resulting unbalances on the induction motor. The system model also provides an insight into the voltages that can appear across the transformer terminals during abnormal operating conditions.